Treatment of ovarian cancer: early stage. - Galdós H., Ricardo (2015)
The ovary being genital gland, represents the essential organ of the woman and as is our understanding, is located in the rectouterina cavity, on the sides of the pelvic excavation in front of the rectum and behind the broad ligaments and fallopian , site which they reached the ninth month of pregnancy. Usually it is 8 or 10 mm below the upper narrow pelvis and 1 or 2 cms. above and ahead of the piriformis; its shape is ovoid, somewhat flattened, and their size varies according to age and physiological status of women. All these anatomical features make inaccessible organ ovary and many pathological spring further from the viewpoint of malignancies surprises.